Elaphoglossum maya and E. rojasii (Dryopteridaceae), replacement names for E. angustifrons and E. reptans, respectively - Túlio L. Pena, Nelson; Freitas, Joelcio; Alves-Araújo, Anderson (Phytotaxa, 2017)
Elaphoglossum Schott ex J.Sm. (in Smith 1841: 148) is a worldwide genus and comprises about 600 species. A total of 450 species is recorded in the Neotropics which is believed to be the diversity center of the genus (Mickel & Smith 2004). They are primarily epiphytic species, but terrestrial or rupicolous lifeforms are found as well (Tryon & Tryon 1982). Elaphoglossum is one of the largest genera of ferns and taxonomically is challenging as to species identification (Lóriga et al. 2013).